Pengembangan Media Pembelajaran Counting Box pada Pembelajaran Matematika Materi Pengurangan Kelas 2 SD - Apreasta, Lika; asmaryadi, Ahmad Ilham; angraini, Deri (Universitas Batanghari Jambi, 2024)
This research is motivated by the fact that many students still have difficulty understandingsubtraction material and in the learning process teachers only use the lecture method and also use whiteboardsand books. In this way, students become inactive and find it difficult to understand the material presentedduring the learning process and make students bored in class when studying subtraction material. This type ofresearch is R&D (Reseach & Development) research with the development model being the 4D model (Define,Design, Develop, Disseminate). Then data collection techniques use observation techniques, interviewtechniques, documentation techniques, question test techniques, and questionnaire techniques. Based on theresults of the validation of the counting box learning media, after analyzing the overall average of theassessments, a valid category can be obtained. Based on the results of this validation, it can be concluded thatthis practicality instrument is suitable for use. Furthermore, from the results of the practicality of the countingbox learning media obtained from the results of the teacher response questionnaire and student responsequestionnaire, the class 2 teacher based on the results of the practical assessment by the class 2 teacherobtained the very practical category. And, the effectiveness of the counting box learning media can be seenfrom the learning results of class 2 students at SDN 06 Koto Baru, with a total of 21 students, whether thestudents are able to achieve the specified KKM. Based on research that has been determined, the percentage ofeffectiveness results seen from student learning outcomes is declared effective